Entre el hogar y el trabajo. Mujeres asalariadas en la agricultura del Valle de Uco, provincia de Mendoza, Argentina - Mingo, Elena (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This article analyze female wageworkers participation in agricultural sector of Uco‟s Valley, in Mendoza, Argentine, considering his linkages with house work and with households female wageworker‟s features.To follow this objective, I study relationship between wageworker life‟s histories and their labor paths, to understand the way in which different life‟s stages modify their possibilities of getting a job and the way in which women develop several strategies to make compatible wage work with house work and reproduction work.This article is part of research‟s advances emerged from three fieldwork‟s stages in Uco‟s Valley region, which consisted in making interviews to employers and female wageworkers life‟s histories to know their labor paths related to their life‟s stages.